Mechanism of Macrophage-Derived Chemokine/CCL22 Production by HaCaT Keratinocytes - Yano, Chizuko (Ann Dermatol, 2015)
BACKGROUND: CC chemokine ligand 17 (CCL17) and CCL22 are the functional ligands for CCR4. We previously reported that inhibitors of nuclear factor-kappa B and p38 mitogen-activated protein kinase (p38 MAPK), but not of extracellular signal-related kinase (ERK), inhibited tumor necrosis factor (TNF)-α- and interferon (IFN)-γ-induced production of CCL17 by the human keratinocyte cell line, HaCaT. Further, an inhibitor of epidermal growth factor receptor (EGFR) enhanced the CCL17 production by these keratinocytes. OBJECTIVE: To identify the mechanism underlying CCL22 production by HaCaT cells. METHODS: We investigated the signal transduction pathways by which TNF-α and IFN-γ stimulate HaCaT cells to produce CCL22 by adding various inhibitors. RESULTS: TNF-α- and IFN-γ-induced CCL22 production was inhibited by PD98059, PD153035, Bay 11-7085, SB202190, c-Jun N-terminal kinase (JNK) inhibitor II, and Janus kinase (JAK) inhibitor 1. CONCLUSION: Our results indicate that CCL22 production in HaCaT cells is dependent on ERK, EGFR, p38 MAPK, JNK, and JAK and is mediated by different signal pathways from those regulating CCL17 production. Altogether, our previous and present results suggest that EGFR activation represses CCL17 but enhances CCL22 production by these cells.